Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk Sari Roti di Kampung Cisadaria - Muhamad, Irgi; Halim, Hartanto; Herlina, Ellin (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to measure the effect of product quality and price partially and simultaneously on purchasing decisions for Sari Roti products, with a case study of consumers in Kampung Cisadaria. The results showed that the regression equation obtained was Y = 0.5613 + 0.511 X1 + 0.300 X2. Partially, each variable (product quality and price) influences purchasing decisions, as evidenced by the t-count which is greater than the t-table and a significance value of less than 0.1. Simultaneously, the product quality and price variables also influence purchasing decisions, with an F-count value of 218.145 which is greater than the F-table of 3.108 and a significance value of 0.000. Based on the determination coefficient test, the R-square value partially influences product quality by 79.2% and price influences by 60.5% partially. And based on the determination coefficient test, the adjusted R-square value obtained was 83.8%, while the remaining 16.2% was influenced by other factors not examined in this study. Based on the results of this study, it can be concluded that product quality has a fairly large influence compared to price. Therefore, companies need to pay more attention to determining the price of Sari Roti products. For example, by conducting a survey of the average economic conditions of the community before determining the price of Sari Roti products.